PENGARUH PRODUCT QUALITY, SERVICE QUALITY DAN ATMOPHARE TERHADAP EMOTION DAN BEHAVIORAL INTENTION DI HERO SUPERMARKET - REZA C, FRANSISCUS BISMOADI (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Development of the retail company is currently growing so that companies compete to provide services and retail formats are also needed at this time to seek new customers and seeing the emotions of the consumer. One of these is the HERO supermarket which is a global retail presence throughout the world. The purpose of this study was to determine the effect of Product Quality, Atmosphere and Service Quality through Positive Emotion and Negative Emotion on Behavioral Intention on supermarket HERO. Techniques used in the sampling in this study were non-probability sampling. Meanwhile, the analytical techniques used are using Structural Equation Modeling (SEM) with Analysis of Moment Structure program. Respondents were drawn from all consumers HERO supermarket.The results showed that there is influence of Product Quality, Atmosphere and Service Quality of the Positive Emotion, Negative Emotion and Behavioral Intention.